Etika Komunikasi dalam Kitab Adab Addunya Waddin Karya Al-Mawardi: Sebuah Studi Hermeneutika - Ahmad Alwajih (Jurnal Komunikasi, 2011)
Ethics in the concept of Al-Mawardi lay as a foundation of fundamental human piety. It also touches an important aspect of life. Within the scope of communication, ethics, according to Al Mawardi, is an effort to clean up human behavior from loss and abuse. When mapped in contemporary science, thought of Al-Mawardi was not fully representative of modernism or postmodernism. However, it's not a final concept if it's read with hermeneutics methods, which refer to Paul Ricouer's model. This article will find how the concept of ethics is explained in the book and the way to read the concept of ethics in science communication.